Decoration of silver and silver oxide nanoparticles on a magnetic albumin modified Chitosan support and its catalytic efficiency investigation - Nazi Salekmokhtari; Fatemeh Rafiee (Scientific Reports)
Abstract In the present study, the magnetic chitosan cross-linked with oxidized chitosan biopolymer was modified with bovine serum albumin protein. Then, the prepared magnetic biosupport was treated with AgNO3 solution under ultrasonic irradiation. After that Ag decoration on the magnetic BSA-modified chitosan support surface, the obtained Fe3O4@BSA-CS@Ag/Ag2O nanocomposite was characterized by various techniques including FT-IR, FE-SEM, TEM, EDS, XRD, VSM, BET and ICP. This nanocatalyst showed excellent efficiency in the reduction reaction of nitroarenes and organic dyes containing methylene blue, methyl orange, and rhodamine B. The advantages of this catalytic system is high conversion at short reaction times using a small amount of silver-based catalyst, easy separation of the catalyst from the reaction mixture with an external magnet and its reusability in the reduction reaction.